CORE COMPETENCIES IN DROPLET-TRANSMITTED INFECTIONS FOR NURSING STUDENTS: A DELPHI STUDY TO ESTABLISH AN EMERGENCY EDUCATION FRAMEWORK IN MACAO (Lex localis - Journal of Local Self-Government, 2025)
Introduction and aim: The escalating threat of droplet-transmitted infectious diseases, exemplified by the SARS and COVID-19 pandemics, has exposed critical vulnerabilities in global health preparedness. A significant gap persists in standardized, contextually-relevant emergency nursing education for undergraduate students, particularly in densely populated regions like Macao. This study aimed to develop and validate, through expert consensus, a scientifically rigorous educational framework to equip future nurses with the essential competencies to manage droplet-transmitted infectious disease emergencies.Material and methods: This study employed a rigorous, multi-round modified Delphi method. An initial 58-item framework was systematically developed by synthesizing evidence from a comprehensive literature review and qualitative insights from preliminary interviews with eight clinical and academic experts. This framework was then subjected to a formal two-round Delphi consultation with a panel of ten distinguished experts in infectious disease control, emergency nursing, and nursing education to achieve consensus on its structure and content. Consensus criteria were stringently defined as a mean item score of ≥ 4.0 (5-point scale), a Coefficient of Variation (CV) of ≤ 0.25, and a statistically significant Kendall's W.Results: A robust consensus was achieved. The iterative process resulted in a finalized, three-tier framework comprising six core modules and 56 validated Level 3 items. The final round demonstrated a significant and improved level of expert agreement (Kendall's W = 0.454, p < .001). Crucially, all 56 final items met the stringent consensus criteria, with CV values ranging from an excellent 0.00% to 16.35%, and the percentage of scores ≥ 4.0 ranging from 88.9% to 100.0%. These results confirm the framework's high internal consistency and strong validation by the expert panel.Conclusion:  This study culminates in the development of a scientifically validated and contextually relevant educational framework that addresses a critical deficit in nursing education. More than just a curriculum, this framework provides a replicable, evidence-based model for nursing education reform, designed to bridge the gap between academic theory and the practical demands of frontline emergency response. Its adoption can significantly enhance the preparedness and competence of future nursing professionals, thereby strengthening the resilience of public health systems against future respiratory-based pandemic threats.